2008
DOI: 10.1080/08860220802406369
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Low-Dose Cholecalciferol and Calcium Treatment on Posttransplant Bone Loss in Renal Transplant Patients: A Prospective Study

Abstract: Background/Aim. Posttransplant steroid doses have been reduced with the use of new and potent immunosuppressive agents. However, posttransplant osteoporosis is still a serious problem. Our aim in this study was to investigate the effect of low-dose cholecalciferol and calcium supplementation on bone loss after transplantation in renal transplant patients. Methods. Fifty-eight renal transplantation patients were included in the study. Fourteen newly transplanted patients (group 1) and 44 renal transplantation p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 35 publications
(51 reference statements)
0
13
0
Order By: Relevance
“…As far as this issue is concerned, it has been hypothesized that a full vitamin D replacement could not substantially decrease PTH levels in renal transplant allografts, given the multifactorial origin of the persistent secondary hyperparathyroidism in this setting 22. In contrast, a number of perspective studies found that cholecalciferol and calcium treatment may markedly reduce PTH levels after renal transplantation 42, 43. Even if PTH‐lowering cholecalciferol effects need further evaluation, this therapy seems to be a promising option.…”
Section: Discussionmentioning
confidence: 99%
“…As far as this issue is concerned, it has been hypothesized that a full vitamin D replacement could not substantially decrease PTH levels in renal transplant allografts, given the multifactorial origin of the persistent secondary hyperparathyroidism in this setting 22. In contrast, a number of perspective studies found that cholecalciferol and calcium treatment may markedly reduce PTH levels after renal transplantation 42, 43. Even if PTH‐lowering cholecalciferol effects need further evaluation, this therapy seems to be a promising option.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have also examined the influence of vitamin D or its derivatives on vaccine responses in humans, mainly conducted in immunocompromised patients, in particular patients on haemodialysis, because vitamin D deficiency is common in this group. The administration of calcitriol at a site adjacent to influenza vaccination did not enhance humoral immunity in these subjects 153 . Vitamin D‐based therapies at earlier stages of chronic kidney disease may impact the immune status of patients who progress to require dialysis or transplantation 154 .…”
Section: Further Directions and Concluding Remarksmentioning
confidence: 98%
“…Since nutritional vitamin D supplement can provide the subst rate (25OHD) for 1,25OH2D production, the decrease in PTH level was observed after cholecalciferol 25000 IU/mo or 400 IU/d supplementation. However, the benefit of nutritional vitamin D in preservation of bone mass was inconsistent [82,83] .…”
Section: Vitamin Dmentioning
confidence: 99%